Offshore wind power : reliability, availability and maintenance - Tavner, Peter J., 1946- (Energy Engineering, 2021)
The new, thoroughly revised edition of this classic book on offshore wind farm reliability. This work captures the latest developments in turbine and farm design, monitoring, safety and maintenance of a centre pillar of the emerging carbon free energy system.